2015
DOI: 10.1038/ijos.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, p21 CIP1/WAF1 and eIF4E in the adjacent tissues of oral squamous cell carcinoma: establishing the molecular boundary and a cancer progression model

Abstract: The present study evaluated the expression of key molecules and the status of DNA in both oral squamous cell carcinoma (OSCC) and adjacent tissues to establish a molecular surgical boundary and provide a cancer progression model. Biopsy samples from 50 OSCC patients were divided into T (cancer), P1 (0–0.5 cm), P2 (0.5–1 cm), P3 (1–1.5 cm) and P4 (1.5–2 cm) groups based on the distances from the visible boundary of the primary focus. Twenty samples of normal mucosa were used as controls. We used immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
(35 reference statements)
3
20
0
Order By: Relevance
“…Despite the better understanding of the mechanisms responsible for cancer progression in recent years, the five-year survival rate of OSCC patients remains less than 50% throughout the world 16,17 . Based on this, molecular studies represent a useful tool to evaluate the role of proteins in the aggressiveness of human malignancies 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the better understanding of the mechanisms responsible for cancer progression in recent years, the five-year survival rate of OSCC patients remains less than 50% throughout the world 16,17 . Based on this, molecular studies represent a useful tool to evaluate the role of proteins in the aggressiveness of human malignancies 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, molecular studies represent a useful tool to evaluate the role of proteins in the aggressiveness of human malignancies 17,18 . In this study, we explored two important proliferation markers (Ki-67 and MCM3) in OSCC samples and their relation to clinical features and survival rates in order to obtain more accurate information about the clinical importance of these proteins in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor protein p53 can control the expression of the p21 gene, which mediates the p53‐dependent cell cycle G 1 phase arrest in response to a variety of stimuli . However, in post‐mitotic differentiated cells, such as spinous cells in squamous epithelia, p21 expression is differentiation‐dependent rather than p53‐dependent . It has been found that p21 expression is independent of the presence of functional p53 in HNSCC, but its expression is related to the differentiation of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the expression of p21 in OSCC . However, no consensus has been reached about its possible clinical significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation